The MADS-Box Transcription Factor CaRIN Positively Regulates Chlorophyll Degradation During Pepper (Capsicum annuum L.) Fruit Ripening by Repressing the Expression of CaLhcb-P4 - Yingying Song; Qing Cheng; Xingzhe Li; Shijie Ma; Huolin Shen; Liang Sun (Plants)
Pepper (Capsicum spp.) is an important global vegetable and spice, with fruit color being a key determinant of its commercial quality. However, the regulatory mechanisms underlying pepper fruit color are still not fully understood. This study focuses on the MADS-RIPENING INHIBITOR (MADS-RIN), a MADS-box transcription factor that regulates various aspects of fruit ripening, including pigmentation. We identified CaRIN, a homolog of tomato’s SlRIN, whose expression is closely associated with fruit ripening in pepper. Silencing CaRIN through virus-induced gene silencing (VIGS) resulted in increased chlorophyll and chlorophyll a content, reduced carotenoid accumulation, and uneven fruit coloration. Integrative analysis of the RNA-seq and DAP-seq data identified 77 target genes regulated by CaRIN, which was involved in processes such as chlorophyll metabolism and plant hormone signaling. Yeast one-hybrid (Y1H) and dual-luciferase (LUC) assays demonstrated that CaRIN directly bound to the promoter of CaLhcb-P4, repressing its expression. Downregulation of CaLhcb-P4 in pepper fruits via VIGS accelerated chlorophyll degradation. Additionally, CaRIN indirectly regulated multiple genes associated with chlorophyll and carotenoid metabolism, sugar transport, and cell wall degradation. These findings provide novel insights into the regulatory mechanisms of chlorophyll degradation during pepper fruit ripening, offering a foundation for further research and potential genetic improvement strategies.